The temple in early Christianity : experiencing the sacred - Regev, Eyal (Anchor Yale Bible reference library., 2019)
"The first scholarly work to trace the Temple throughout the entire New Testament, this study examines Jewish and Christian attitudes toward the Temple in the first century and provides both Jews and Christians with a better understanding of their respective faiths and how they grow out of this ancient institution. The centrality of the Temple in New Testament writing reveals the authors' negotiations with the institutional and symbolic center of Judaism as they worked to form their own religion." -- Publisher description.